PENANAMAN KARAKTER DISIPLIN PADA INTERAKSI SOSIAL SISWA SEKOLAH DASAR - Wanda Hardianti Sukma; Nilam Ismi Saraswati; Nadia Setiawati (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The main problem in the character of discipline is the tendency to lack discipline. Illegal activities that cause environmental disasters, traffic accidents, and landslides are more likely to occur due to a lack of law enforcement. Several violations also happened in the school environment, such as being late for class, truancy, not doing assignments, not wearing uniforms according to the rules, and other violations. This is a severe problem because discipline is one of the success factors in learning. Data collection techniques in this study include observation at the research site. The observation method is the experience and systematic recording of the symptoms that appear on the research object. Researchers must use the observation method to collect data other than interviews. Evaluation is done by giving advice and motivation on weekends. In addition, the teacher also reports every attitude and behavior of students at school to parents/guardians of students when holding regular meetings. The goal is that parents/guardians also educate and teach character values ​​at home and carry out intensive supervision at home. The teacher grades every weekend. Students are encouraged to be better than yesterday during evaluation activities. In addition, when holding regular meetings with parents/guardians of students, teachers will meet with parents at school to report on student attitudes and behavior